Granulomatous Secondary Syphilis: A Case Report with a Brief Overview of the Diagnostic Role of Immunohistochemistry - Francesca Ambrogio; Gerardo Cazzato; Caterina Foti; Mauro Grandolfo; Gisella Biagina Mennuni; Gino Antonio Vena; Nicoletta Cassano; Teresa Lettini; Cosimo Castronovi; Vito Ingordo; Paolo Romita; Raffaele Filotico (Pathogens, 2023)
The diagnosis of syphilis can be challenging for dermatologists and dermatopathologists. In particular, secondary syphilis can have different clinical and histopathological presentations. A granulomatous tissue response is an unusual finding in secondary syphilis. We report the case of a 77-year-old man who presented with a 4-week history of non-pruritic generalised macules, papules, nodules and plaques. Histopathologically, there was a dense perivascular and periadnexal lympho-histiocytic dermal infiltrate with non-palisading and non-caseifying epithelioid granulomas and abundant plasma cells. The diagnosis of syphilis was confirmed by serology and immunohistochemical detection of Treponema pallidum in the biopsy specimen. A brief overview of the diagnostic role of immunohistochemistry is also provided, with particular emphasis on reported cases of granulomatous secondary syphilis.